(untitled) (PerCursos, 2023)
The present manuscript brings a reflection on the construction of the phenomenon of Homeless Population and the relationship with the history of the black population in Brazil. The article composes the ongoing research of the authors in the PostGraduate Program in Social Work at Universidade Estadual Paulista. We chose the method in Marx to carry out an analysis of the enslavement process as a central component for the emergence and expansion of Late Capitalism throughout Latin America. Through a brief rescue of historical and legal landmarks, it reflects on the profile and identities attributed to the PSR and its deep relationship with the country’s slavery and racist history. It is concluded that the phenomenon of the Homeless Population imposes great challenges to the reality of urban spaces, and that the social movements of this segment have an extensive agenda for the realization of Human Rights, therefore it is fundamental to understand the complexity of this reality, to know the historical process of this phenomenon, as well as carrying out more research and data collection that may contribute to the instrumentalization of the struggles and resistance of this population.